Activity of ion channels during volume regulation by clonal N1E115 neuroblastoma cells. - Falke, L C (1989)
When exposed to a hypotonic bathing solution, clonal N1E115 neuroblastoma cells initially swell and then undergo a regulatory volume decrease (RVD). Using cell-attached patch-clamp recording, we have found that the activity of a stretch-sensitive, nonselective cation [C+(SA)] channel increases shortly after the onset of osmotically induced cell swelling; this depolarizes the cells as much as 30 mV. Shortly thereafter, and roughly coincident with the onset of RVD, two types of voltage-dependent channels open at the new resting potential; these are (i) a delayed-rectifier type K+ [K+(DR)] channel and (ii) a large-conductance anion channel. We suggest that opening of the C+(SA) channel may contribute to the volume "sensor" mechanism, while the depolarization-induced opening of the K+(DR) and anion channels may constitute a significant K+ salt exit pathway, operating in RVD.